Efeitos ocasionados pelo uso da água tratada por campo mag-nético na produção de concreto utilizando cimento cp v-ari - Targino, Alex de Paiva (Universidade Federal Rural do Semi-Árido, 2018)
The use of magnetism in everyday life is becoming more and more present, and can occur in various forms, whether through communication devices such as cell phones, computers and data storage in computer, image analysis or cure of diseases in bio-technology and even in agriculture, as in the germination of seeds and the biological development of plants. One industry that has been beginning to study the effects of this application in their area is civil engineering, verifying various ways of water treat-ment. According to the studies carried out, the surface tension of the water is reduced, providing a better hydration of the cement, as well as a break in the calcium hydroxide compounds (causing greater adhesion in the regions where they are located), which ends up affecting the gain of resistance. In this work, it was analyzed the use of the treated water by magnetic field in the concrete using the CP-V-ARI cement. For this purpose, the compressive strength and the workability of the concrete produced after a water treatment by magnetic field, in a static manner, with magnets of different ge-ometries were used as response function for data analysis. From this perspective, the results showed improvements in compressive strength and an increase in workability (only for L geometry in cone truncation), in both geometries to the rupture of the 7-day cure’s specimens. For the rupture at 28 days only the bodies treated with magnets of geometry L presented good results. In this way, although it is still an exploratory phase, which may become a production technique, it is already favorable with an increase of more than 8% in resistance and 18% in the workability using neodymium magnets, providing good concrete performance above that commonly obtained at construction sites. Keywords:
Monografia
Keywords: Incorporação no concreto; Tratamento magnético da água; Resistência à compressão; Trabalhabilidade; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA